Daqqotu Adillati Nikâhi Al-Mar'ah Al-Hâmil Az-Zâniyah 'Inda Fiqhi Al-Munâkahât (Ad-Dirâsah 'Ala Ârâ'i Al-'Ulamâ Al-Madzâhib - Husnul Yaqin (Jurnal Hikmatuna, 2017)
Fuqaha have differences of opinion in determining the legal ruling of marriage for a pregnant woman outside of wedlock. Firstly, the Hanafi school permits the marriage of a woman who has committed adultery. If the woman is pregnant, then sexual relations are not allowed until the child is born. Secondly, the Malik school prohibits marrying a woman who has committed adultery, whether she is pregnant or not. Thirdly, the Shafi'i school allows the marriage of a woman who has committed adultery, whether she is pregnant or not, and it is permissible for the man who impregnated her or another man to marry her. It is also permissible to marry the mother and daughter of a woman with whom one has committed adultery. Fourthly, the Hanbali school holds the opinion that marrying a woman who has committed adultery is not permissible, except under two conditions: the completion of her waiting period (iddah) and sincere repentance.